2007
DOI: 10.1515/crelle.2007.045
|View full text |Cite
|
Sign up to set email alerts
|

The colored Jones polynomials of the figure-eight knot and its Dehn surgery spaces

Abstract: We calculate limits of the colored Jones polynomials of the figureeight knot and conclude that in most cases they determine the volumes and the Chern-Simons invariants of the three-manifolds obtained by Dehn surgeries along it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…See, for example, [20] about recent developments of the conjecture and its generalizations. As one of the generalizations, Yokota and the author [22] proved that for the figure-eight knot the coloured Jones polynomial contains much more information. Actually, we showed that if we perturb the parameter 2π √ −1 a little, then the corresponding limit determines the SL(2; C) Chern-Simons invariant associated with an irreducible representation of π 1 (S 3 \ K) to SL(2; C) in the sense of Kirk and Klassen [15].…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, [20] about recent developments of the conjecture and its generalizations. As one of the generalizations, Yokota and the author [22] proved that for the figure-eight knot the coloured Jones polynomial contains much more information. Actually, we showed that if we perturb the parameter 2π √ −1 a little, then the corresponding limit determines the SL(2; C) Chern-Simons invariant associated with an irreducible representation of π 1 (S 3 \ K) to SL(2; C) in the sense of Kirk and Klassen [15].…”
Section: Introductionmentioning
confidence: 99%
“…The original volume conjecture (Conjecture 0.1) for the figure-eight knot was prove by T. Ekholm (see for example [30]). Conjecture 0.2 was proved by Yokota and the author [35] in the case of the figure-eight knot. The following theorem appears in [33], proving Conjecture 0.3.…”
Section: Topological Interpretation Of the Asymptotic Expansion Of Thmentioning
confidence: 90%
“…The conjecture is true for the figure-eight knot [35]. This means that for large N we can write for a complex function S(u).…”
mentioning
confidence: 94%
“…It was demonstrated [8,22] that the A-polynomial has a relationship with an asymptotic limit of the colored Jones polynomial for a case of the figure-eight knot. Our purpose in this article is to show that this correspondence is also supported for a case of the twist knots and the torus knots.…”
Section: Imentioning
confidence: 99%